Security Analysis of DSR and DSDV Protocol in Wireless Sensor Networks - Taneja, Kriti (My University, 2017)
Wireless Sensor Networks are deployed in various application areas such as healthcare, military, agriculture, home automation, etc. Security of WSNs has become crucial issue because of the transmission of sensitive data through the systems integrated with WSN architecture. Many methods has been developed to secure computer networks and communications over internet, but WSN requires different security mechanism because of its unique architecture and the constraints it faces. Intrusion detection method is one such method which has gained importance over the past few years. An Intrusion detection system gathers the information from various devices within a network and analyz es that information to identify any possible security threats. There are different techniques of intrusion detection which are discussed in this thesis. Anomaly detection technique has been implemented in the thesis to detect intruder in the network. WSN routing protocols are classified into various types, that are, mode of function, type of network structure and participation styles of nodes. Mode of function is further classified into reactive, proactive and hybrid. DSR and DSDV routing protocols, which are reactive and proactive protocols respectively, are simulated in a network in this thesis. The main objective of this thesis is to do a comparative study of network behavior of DSR and DSDV protocol with intrusion and without intrusion. This comparison is done because anomaly intrusion detection technique has been applied. The evaluation metrics on the basis of which performance is compared are throughput, packet ID of received data packets and cumulative sum of lost bytes. this performance evaluation i s done using trace graph tool in NS - 2 network simulator. Furthermore, the dataset generated after simulation is deeply analyzed on a machine learning tool, by processing the data on different classification algorithms to obtain the results.
Master of Technology -CSA
Keywords: DSR; DSDV; Wireless Sensor Network; Security; NS2; Learning Algorithms